Initial Experience with the Coaxial Dual-Lumen Ascent Balloon Catheter for Wide-Neck Aneurysm Coil Embolization - Lazzaro, Marc A.; Darkhabani, Ziad; Zaidat, Osama O.; Fitzsimmons, Brian-Fred M. (Frontiers in Neurology, 2011)
Introduction: Techniques for coil-embolization of wide-neck cerebral aneurysms include the use of stents and temporary occlusion with compliant non-detachable balloons to safely allow dense packing of the aneurysm lumen with detachable coils. We describe the use of a new balloon device for assisting in wide-neck aneurysm coil treatment. Methods: A single institution neuroendovascular database was accessed to identify cases in which the Ascent balloon (Codman Neurovascular, Raynham, MA) was used for aneurysm coil embolization. Clinical, demographic, and angiographic data were obtained through chart review. Results: Eleven cerebral aneurysm cases were treated using the Ascent balloon during the first twelve-month period that the new device was available at our institution. Three of the patients presented with ruptured aneurysms. All aneurysms were large (maximum diameter 6 mm or greater), with an average maximum diameter of 9.4 mm, and an average neck diameter of 5.5 mm. Complete occlusion with coil embolization (Raymond class I) was achieved in all cases. The Ascent balloon was successfully positioned across the neck of the aneurysm in 9 patients. Conclusions: This initial experience demonstrates the feasibility and immediate outcomes of the coaxial dual-lumen design Ascent balloon catheter used as an assistive device in coil embolization of wide-neck cerebral aneurysms. This device contributes to the growing number of assistive devices for the treatment of complex cerebral aneurysms.